Laser based digital pen with multi-purpose mouse functionality - Chowdhury, Asef Sharar; Jaber, Rishad Mubtasim; Alam, Md. Towfiqul; Nayeem, Jannatul (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.